Origins and functions of eosinophils in two non-mucosal tissues - Day, Katie S.; Rempel, Lucas; Rossi, Fabio M. V.; Theret, Marine (Frontiers in Immunology, 2024)
Eosinophils are a type of granulocyte named after the presence of their eosin-staining granules. Traditionally, eosinophils have been best known to play prominent roles in anti-parasitic responses and mediating allergic reactions. Knowledge of their behaviour has expanded with time, and they are now recognized to play integral parts in the homeostasis of gastrointestinal, respiratory, skeletal muscle, adipose, and connective tissue systems. As such, they are implicated in a myriad of pathologies, and have been the target of several medical therapies. This review focuses on the lifespan of eosinophils, from their origins in the bone marrow, to their tissue-resident role. In particular, we wish to highlight the functions of eosinophils in non-mucosal tissues with skeletal muscle and the adipose tissues as examples and discuss the current understanding of their participation in diseased states in these tissues.